Cooperatives as key drivers of commercialization, empowering communities and improving income and livelihoods in Ethiopia - Getachew, Tesfaye; Rischkowsky, Barbara A.; Belay, Berhanu; Rekik, Mourad; Haile, Aynalem (International Livestock Research Institute, 2024)
The Community-Based Breeding Program (CBBP) for sheep and goats, launched in Ethiopia in 2009, represents a paradigm shift in traditional breeding approaches. It offers an innovative alternative that moves away from centralized nucleus systems and exotic crossbreeding, instead focusing on improving local breeds to enhance productivity, boost incomes, and contribute to food security. (Haile et al., 2011, 2023). Designed to address the unique needs of smallholder livestock producers, CBBP emphasizes improving local breeds to enhance productivity, boost incomes, and contribute to food security. By fostering strong community involvement and leveraging indigenous knowledge, the program ensures sustainable genetic improvement, income increment, and livelihood improvement while promoting community ownership (Haile et al., 2020; Kassie et al., 2021). A cornerstone of CBBP is the establishment of breeder cooperatives, which play a crucial role in managing resources and implementing the breeding program effectively. These cooperatives oversee activities such as the selection and use of communal breeding sires, approval of superior sires, facilitating the sale of breeding rams to production units, and coordinating the culling of suboptimal animals. This model not only strengthens community participation but also supports the development of a replicable framework for livestock improvement that is relevant both within Ethiopia and beyond (Haile, 2017).